2011
DOI: 10.1164/rccm.201008-1303oc
|View full text |Cite
|
Sign up to set email alerts
|

A Central Role for CD68(+) Macrophages in Hepatopulmonary Syndrome

Abstract: Rationale: The etiology of hepatopulmonary syndrome (HPS), a common complication of cirrhosis, is unknown. Inflammation and macrophage accumulation occur in HPS; however, their importance is unclear. Common bile duct ligation (CBDL) creates an accepted model of HPS, allowing us to investigate the cause of HPS. Objectives: We hypothesized that macrophages are central to HPS and investigated the therapeutic potential of macrophage depletion. Methods: Hemodynamics, alveolar-arterial gradient, vascular reactivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
136
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(151 citation statements)
references
References 44 publications
(51 reference statements)
7
136
0
8
Order By: Relevance
“…[35][36][37] Data from animal models of HPS suggest a central role for pulmonary intravascular macrophages through generation of inducible nitric oxide synthase, vascular endothelial growth factor, and platelet-derived growth factor. 35,38,39 Inhibition of nitric oxide synthase, the endothelin-B receptor, and vascular endothelial growth factor has mitigated HPS in animal models. [40][41][42] Notably, these same mediators have also been implicated in POPH and endothelin receptor antagonists (dual and selective), and phosphodiesterase-5 inhibitors are mainstays of therapy for PAH and POPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37] Data from animal models of HPS suggest a central role for pulmonary intravascular macrophages through generation of inducible nitric oxide synthase, vascular endothelial growth factor, and platelet-derived growth factor. 35,38,39 Inhibition of nitric oxide synthase, the endothelin-B receptor, and vascular endothelial growth factor has mitigated HPS in animal models. [40][41][42] Notably, these same mediators have also been implicated in POPH and endothelin receptor antagonists (dual and selective), and phosphodiesterase-5 inhibitors are mainstays of therapy for PAH and POPH.…”
Section: Discussionmentioning
confidence: 99%
“…14 Additionally, a substantial degree of overlap has been described in the histologic findings of each condition. Thenappan et al 38 identified a proliferative vasculopathy in the small pulmonary arteries of a rat model of HPS, alongside the characteristic changes of HPS such as vasodilatation and neoangiogenesis. Similarly, dilated arterial segments have been observed proximal to plexogenic vascular lesions in PAH with and without liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…A local increase in pro-inflammatory mediators and pulmonary intravascular sequestration of macrophages leading to an increase in iNOS activity and NO production has also been described [70]. This may be caused by bacterial translocation and systemic endotoxaemia and, presumably, it is largely mediated by tumour necrosis factor-a [71,72]. Other mechanisms/associations identified to date through human or experimental studies include increased angiogenesis through upregulation of the vascular endothelial growth factor, increased carbon monoxide production through haem oxygenase, and increased levels of oestrogen and progesterone.…”
Section: Pathophysiologymentioning
confidence: 99%
“…ET-1 levels were found to be elevated in cirrhosis and IPVD cases [9]. Macrophages could also induce vasodilatation due to heme oxygenase (HO-1) production that resulted in increased production of carbon monoxide (CO) [11]. Furthermore, gene polymorphisms also played a role in angiogenesis that had been linked with advanced HPS [12].…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%